Preschoolers’ free play - connections with emotional and social functioning - Guida Veiga; Carlos Neto; Carolien Rieffe (International Journal of Emotional Education, 2016)
Play has an important role in various aspects of children’s development. However, time for free play has declined substantially over the last decades. To date, few studies have focused on the relationship between opportunities for free play and children’s social functioning. The aims of this study are to examine whether children´s free play is related to their social functioning and whether this relationship is mediated by children´s emotional functioning. Seventy-eight children (age, 55- 77 months) were tested on their theory of mind and emotion understanding. Parents reported on their children’s time for free play, empathic abilities, social competence and externalizing behaviors. The main findings showed that free play and children’s theory of mind are negatively related to externalizing behaviors. Empathy was strongly related to children’s social competence, but free play and social competence were not associated. Less time for free play is related to more disruptive behaviors in preschool children, however certain emotional functioning skills influence these behaviors independently of the time children have for free play. These outcomes suggest that free play might help to prevent the development of disruptive behaviors, but future studies should further examine the causality of this relationship.